A cross-sectional study of inpatients with late stage of dementia in Southeast China and the associations between biochemical parameters and apolipoprotein E genotypes - Jiang B; Zhang XP; Chen MF; Wang Z; Zhao MX; Chen BH; Li HL (Clinical Interventions in Aging, 2018)
Bin Jiang,1,2,* Xue-Ping Zhang,3,* Mei-Fang Chen,3 Zheng Wang,3 Ming-Xue Zhao,3 Bin-Hua Chen,3 Hong-Lei Li1 1Department of Neurology and Research Center of Neurology, The Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, 2Department of Neurology, The First Affiliated Hospital of Xiamen University, Xiamen, 3The Seventh People’s Hospital of Hangzhou, Mental Health Center of Zhejiang University School of Medicine, Hangzhou, People’s Republic of China *These authors contributed equally to this work Background: The purpose of this study was to analyze the disease distribution of patients in the late stage of dementia through a cross-sectional investigation and to clarify the association between apolipoprotein E (APOE) genotypes and the serum levels of total cholesterol, total triglycerides, and blood glucose in the late-stage Alzheimer’s disease (AD) patients.Methods: Patients who were in the late stage of dementia in a mental health center were enrolled in this study. A broad battery of neuropsychological tests and neuroimaging was applied to make the diagnosis. The APOE genotype was determined by the multiplex amplification refractory mutation system polymerase chain reaction. The association between APOE genotype and the blood level of biochemical parameters was studied.Results: A total of 155 patients were enrolled in this study. The majority of patients had AD (67.8%), followed by vascular dementia (15.5%), mixed dementia (9%), and others (7.7%). The APOE ε4 allele frequency was significantly different in the different groups. The serum level of total cholesterol (TC) in APOE ε4 carriers was higher than in non-carriers (P<0.05). No statistically significant differences were found in the blood glucose and triglycerides (TG) levels between these two groups.Conclusion: To our knowledge, this is the first paper to study the characteristics of late-stage dementia in hospital patients in Southeast China. We found that the disease distribution was quite consistent with previous prevalence studies. Moreover, we found that the serum level of TC was higher in APOE ε4 carriers group. However, no association was found between the APOE ε4 allele and serum levels of glucose, TC and TG in the late stage of AD. Keywords: Alzheimer’s disease, APOE, glucose, cholesterol, triglycerides